Influence of Mobile Internet Services on Base Station Energy Consumption - Wenwen Li; Sen Bian; AunChan Chien; Zecai Shao (Dianxin kexue)
Rapid growth in mobile internet service has broughtsignificant challenges to the mobile operators in terms of network resource utilization and energy consumption.The relationship between mobile services’ characteristics and its impact on network energy consumption is still unclear.In order to accurately assess the impact of mobile serviceson network resourcesand the resulting energy consumption of mobile network equipment，the physical layer resources requirements for various mobile services was measured，and then an improved four-step“Quadratic Linear Mapping”modeling methodology was proposed.11 types of typical services were quantitatively evaluated in terms of network resources and the resulting network energy consumed by data and signaling traffic.The proposed methodology provided a foundational model for mobile operators to develop optimization techniques to reduce the overall energy consumption of provisioning mobile internet services.